ENERGY-BASED MODEL OF A LIQUID PISTON GAS COMPRESSION SYSTEM (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
Compressed air energy storages (CAES) are used in autonomous or semi-autonomous renewable energy systems due to their advantages over battery energy storage, e.g., environmental-friendly production process and sufficiently large number of cycles. Liquid piston (LP) technology for CAES is an alternative to other gas compression technologies developed to provide better heat transfer and thus increase energy efficiency. An energy-based model of a hydropneumatic accumulator using the LP gas compression in a port-Hamiltonian (pH) form is developed for control design. The bond graph framework is utilized to directly derive the equations in the pH form by exploiting the nonlinear fluid capacitance as a storage model. Nonlinearity is depicted analytically for a generalized polytropic process considering the ideal gas condition. The operation of the developed model is validated using MATLAB R2021b Simscape simulations.
Keywords: Compressed air energy storage; Liquid piston; Port Hamiltonian system; Bond graph; Hydropneumatic accumulator; Energy-based model